The Effect of Immigration on Native Self‐Employment - Fairlie, Robert W.; Meyer, Bruce D. (Journal of Labor Economics, 2003)
We examine the impact of immigration on self‐employed natives. In a new general equilibrium model of self‐employment and wage/salary work, a range of plausible parameter values implies small negative effects of immigration on native self‐employment rates and earnings. Using 1980 and 1990 Census microdata, we then examine the relationship between changes in immigration and native self‐employment rates and earnings across 132 of the largest U.S. metropolitan areas. We find evidence suggesting that self‐employed immigrants displace self‐employed natives but do not have a negative effect on native self‐employment earnings. The effects are much larger than those predicted by the theoretical model.